Problems of Determination and Payment of Bankruptcy Administration Costs - Tamošiūnienė, Egidija; Višinskis, Vigintas; Kirkutis, Mykolas; Jokubauskas, Remigijus (Teisė, 2021)
This article continues the research of peculiarities seen in the insolvency proceedings of legal entities and examines the problems of determination and payment of administrative costs of the bankruptcy proceedings of legal entities. The authors analyze the features of these costs in bankruptcy proceedings and how they can be identified. It also assesses the order in which administrative expenses must be paid in cases where the expenses do not exceed the estimate of administrative expenses, exceed it, or if assets of the legal person are insufficient to reimburse these costs.
Keywords: bankruptcy proceedings; costs of administration; effectiveness of bankruptcy proceedings; autonomy of creditors